TEACHING LISTENING AT JUNIOR AND SENIOR HIGH SCHOOLS AS DEMANDED BY CURRICULUM 2013 - Jufri Jufri (International Conference on Languages and Arts, 2014)
This paper is aimed at discussing the way how to teach listening to the students of junior and senior schools as it is demanded by curriculum 2013 nowadays.  Based on the syllabus of curriculum 2013 for both junior and senior high schools, most basic competences are concerning with listening and reading skills. For transactional and interpersonal texts, for instance, listening competences are dominant. As it is known, the four language skills – listening, speaking, reading and writing—are taught by using integrative model.   For this purpose, the lesson might be started with listening or reading, and then integrated to speaking and writing. This condition makes most teachers find difficulties in applying this curriculum in the classroom.  That is why; the teacher should really understand how to integrate these skills in EFL classes. In this paper, it is discussed the way how to teach listening skill and how it is integrated to speaking skill. In curriculum 2013 the teaching paradigm changes from teacher-centered teaching to student-centered model. For this reason, the students should be active, creative and have high fighting spirit in learning English. To do so, the teacher is required to apply scientific approach in which the students are active to seek information by themselves.  For this case, there are three teaching models that are suitable to use, that is, problem-based learning, discovery-based learning and project-based learning. Finally, the teacher’s success in obtaining his/her instructional objectives will be much dependent on activities he/she selects and arranges in the classroom. Keywords: curriculum 2013, EFL, junior high school, senior high school, teaching listening,